1.23 Ga mafic dykes in the North China Craton and their implications for the reconstruction of the Columbia supercontinent - Wang, Wei; Liu, Shuwen; Santosh, M.; Zhang, Lifei; Bai, Xiang; Zhao, Yue; Zhang, Shuanhong; Guo, Rongrong (Gondwana Research, 2015)
The Proterozoic world was shaped by the Paleo-Mesoproterozoic Columbia and Neoproterozoic Rodinia supercontinents. The North China Craton (NCC) is an integral component of Columbia supercontinent assembly, but the lack of rock records in the transitional period between Columbia and Rodinia in the late Mesoproterozoic (1.3-1.2 Ga) has resulted in its exclusion from models that trace the Columbia-Rodinia transition. The paleogeographic position of the NCC is also elusive, with India, Baltica, and Siberia as potential neighbors during the early evolution of Columbia. Here we report the discovery of a suite of similar to 1.23 Ga mafic dykes covering an area of similar to 0.6 x 10(6) km(2) of the NCC. These mafic rocks can be classified into both alkaline and subalkaline groups. The former group may have been derived from lower degrees of partial melting of a depleted asthenospheric mantle with limited involvement of a lithospheric mantle component, whereas the latter group can be modeled by higher degrees of partial melting of a subduction-modified enriched lithospheric mantle. Considering the large areal extent of the 123 Ga mafic dykes, and their dominantly OIB (Ocean Island Basalt)-like geochemical features, a Mesoproterozoic mantle plume regime is invoked for the NCC. Compiling information on global similar to 1.27-121 Ga mafic dykes, flood basalts and layered intrusions, we establish a Mesoproterozoic hotspot track, and consider the NCC to have been located between Laurentia and Baltica. Combined with recent paleomagnetic and geological data, we infer that the Laurentia-NCC-Baltica connection may have existed since the late Paleoproterozoic. We further propose that both plate tectonic (introversion or extroversion) and mantle plume regimes played vital roles during the supercontinent transition. (C) 2014 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved. National Natural Science Foundation of China [41121062, 41272209, 41072143, 40872120]; China Geological Survey [1212011121070] SCI(E) ARTICLE swliu@pku.edu.cn 4 1407-1418 27